The case series of spontaneous hemoperitoneum in third trimester pregnancy - Akriti Gupta; Uttara Gupta; Anand Gupta (Asian Journal of Medical Sciences, 2022)
Spontaneous hemoperitoneum in pregnancy (SHiP) is unprovoked intraperitonealbleeding. It is a rare entity but a life-threatening complication as it is associated with adverse pregnancy outcome. It is a surgical emergency and requireslaparotomy to identify the cause. Complication of pregnancy and spontaneous hemoperitoneum wasincluded in the study, and cases involving pregnancy termination and ectopic pregnancy were excluded from the study.Maternal demographics, description of spontaneous hemoperitoneum, and specifics diagnosis and management were recorded. Data were extracted and entered in reporting forms. Median values were calculated for continuous variables, and percentages were calculated for categorical variables. The authors reported three cases of SHiP were seen. The gestational age of the patient included in the studywas36 weeks, 38 weeks, and 34+6 weeks, respectively. In the first 2 cases, clinical picture was pointing toward maternal hypovolemia while in 1st case ultrasound s/o fetal demise and in the 2nd case, there was fetal distress. In the 3rd mentioned case, fetal distress was observed on the examination, and hemoperitoneum was the incidental finding which was due to endometriosis.The cause of SHiPis rupture of posterior wall of the uterus, rupture of utero-ovarian vessels, and endometriosis.